2021
DOI: 10.1590/s1808-185120212003243743
|View full text |Cite
|
Sign up to set email alerts
|

Lavender Essential Oil for Spinal Pain in Obese Women: A Clinical Trial

Abstract: Objective To analyze the effect of lavender essential oil associated with massage on spinal pain levels in obese women. Methods The sample included 49 obese women, between 20 and 60 years of age, randomly assigned to three groups: control (n=15), intervention (n=19) and placebo (n=15). The intervention and placebo groups were submitted to eight 35-minute sessions, twice a week for one month, but the essential oil of Lavandula angustifolia was used only in the intervention group. A placebo was used for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
0
0
1
Order By: Relevance
“…Furthermore, in the studies listed in this SR, the lavender EO demonstrated benefits for the symptom of anxiety in women with breast cancer, which corroborates other findings in the literature, in which the use of this EO in multiple groups is reported, with the aim of reducing anxiety, calming, relaxing and improving sleep quality [26][27] .…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, in the studies listed in this SR, the lavender EO demonstrated benefits for the symptom of anxiety in women with breast cancer, which corroborates other findings in the literature, in which the use of this EO in multiple groups is reported, with the aim of reducing anxiety, calming, relaxing and improving sleep quality [26][27] .…”
Section: Discussionsupporting
confidence: 86%
“…Além disso, nos estudos elencados nesta RS, o OE Lavanda demonstrou benefícios para o sintoma de ansiedade em mulheres com câncer de mama, o que corrobora com outros achados na literatura, em que se relata o uso deste OE em múltiplos grupos, com a finalidade de reduzir ansiedade, acalmar, relaxar e melhorar a qualidade do sono [26][27] .…”
Section: /14 Discussãounclassified